Enhanced particle transport events approaching the density limit of the J-TEXT tokamak. (24th November 2021) - Long, T.; Diamond, P.H.; Ke, R.; Nie, L.; Xu, M.; Zhang, X.Y.; Li, B.L.; Chen, Z.P.; Xu, X.; Wang, Z.H.; Wu, T.; Tian, W.J.; et al.
Abstract: Enhanced particle transport events are discovered and analyzed as the density limit of the J-TEXT tokamak is approached. Edge shear layer collapse is observed and the ratio of Reynolds power to turbulence production decreases. Simultaneously, the divergence of turbulence internal energy flux (i.e. turbulence spreading) increases, indicating that shear layer collapse triggers an outward spreading event. Studies of correlations show that the enhanced particle transport events are quasi-coherent, and manifested primarily in density fluctuations which exhibit positive skewness. Electron adiabaticity emerges as the critical parameter which signals transport event onset. For α < 0.35 as density approaches the Greenwald density, both turbulence spreading and density fluctuations rise rapidly. Taken together, these results elucidate the connections between edge shear layer, density fluctuations, particle transport events, turbulence spreading and plasma edge cooling as the density limit is approached.